PENERAPAN MODEL PEMBELAJARAN KOOPERATIF ACTIVE KNOWLEDGE SHARING UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ASAM DAN BASA DI KELAS XI SMA NEGERI 2 TAMBANG - Zahera Zahera '; Jimmi Copriady Jimmi Copriady; Abdullah Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Research has been done to get student’s mastery learning with by using model Cooperative Active Knowledge Sharing inclassXI Science SMAN 2 Tambang. This researchis pra-experimentresearchwith one-shot study case design. The sampel use random from the five class XI Science. This research was conducted in class XI Science MIA 5, the for two month’s from january to february 2015. Data analysistechnique by using five formula mastery.mastery individual learning objectives (KTPI), mastery each of the learning objectives (KMTP), classical mastery learning objectives (KTPK), mastery learning of individual (KI), mastery learning classical (CBC). Research for thefinal show that Classical mastery learning objectives 91.67%. and mastery learning classical is 90%. it’s means thatthe application of Cooperative learning model of Active Knowledge Sharingcan achieve student’s mastery learning on the subject of alkaline acid solution inclassXI MIA 5 SMAN 2 Tambang.Keywords: Active Knowledge Sharing, mastery learning, alkaline acid solution